Characterization of imaging latency for real-time MRI-guided radiotherapy. (6th August 2018) - Borman, P T S; Tijssen, R H N; Bos, C; Moonen, C T W; Raaymakers, B W; Glitzner, M
Abstract: Hybrid MR-linac systems can use fast dynamic MR sequences for tumor tracking and adapt the radiation treatment in real-time. For this the imaging latency must be as short as possible. This work describes how different acquisition parameters influence this latency. First, the latency was measured for Cartesian readouts with phase encode orderings linear, reverse-linear, and high-low . Second, the latency was measured for radial readouts with linear and golden angle profile orderings. To reduce the latency, a spatio-temporal (k-t) filter that suppresses the k-space center of earlier acquired spokes was implemented for the golden angle sequence. For Cartesian readouts a high-low ordering achieved a three times lower latency compared to a linear ordering with our sampling parameters. For radial readouts the filter was able to reduce the acquisition latency from half the acquisition time to a quarter of the acquisition time. The filter did not compromise the signal-to-noise ratio and the artifact power.